Recent development of Slovene towns - social structure and transformation - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
In Slovene towns and urban areas several processes of social transformation and change have been present in the last decade. As a consequence of political and economic transition increased socialdifferentiation resulted in increased social segregation in urban areas.Some areas such as high-rise housing estates and part of older inner city areas were affected by social degradation and concentration of low-incomepopulation and ethnical minorities. In some parts of inner cities processes of reurbanisation and gentrification are taking place. However, the degree of social segragation is lower than in the cities of most transitional countries of Central and Eastern Europe.
Keywords: mesta; urbana geografija; urbanizacija; suburbanizacija; urbani razvoj; urbana sociologija; družbeni razvoj; družbena struktura; transformacija; Slovenia; Slovenija